Labour markups in the Polish food sector - Kufel-Gajda, Justyna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2018)
In the period 2000-2013 the Polish agro-food sector enjoyed a very dynamic growth. The research objective was to measure monopolistic markups based on labor input, which indicate the level of market power, with data and improved methodology proposed by Nekarda and Ramey [2013). The research object was the Polish food sector in the period 2002-2013. Taking into account overhead labor, CES production function and marginal wage different from average wage, six adjustments were used. Because of the corrections the average food sector markup increased from 17.7% of price in the baseline scenario to 67.9% of price when three corrections were implemented together. It appeared that the food sector markup in the analyzed period depending on the specification increased by 13.5 to 31.3%. Moreover, markups in the analyzed period proved to behave counter-cyclically regarding the business cycle.
Argumenta Oeconomica, 2018, Nr 2 (41), s. 297-309
Keywords: markups; food sector